COVID-19 and hospital activity: experience of the Nephrology Department of Ibn Sina Hospital-Rabat - Sara El Maakoul; Loubna Benamar; Naima Ouzeddoun; Tarik Bouattar (SpringerOpen, 2024)
Abstract The COVID-19 pandemic has led to a major health crisis, responsible for a very high morbidity in the world. This context represented an organizational challenge and required an adaptation of health services. The purpose of this study is to evaluate the activity of the Nephrology Department of Ibn Sina Hospital of Rabat during the period of confinement of the COVID-19 pandemic. Material and methods Retrospective study of hospitalization, dialysis and consultation activities in the nephrology, and dialysis and kidney transplantation department, during the period of confinement in Morocco from March 12 to June 16, 2020. Results We have identified, for the considered period of three months, 65 patients hospitalized in the nephrology department versus 218 patients during the 3 months preceding the start of confinement in Morocco, which corresponds to a decrease of 70%. The mean age of the patients was 50 ± 16 years with a male predominance. Kidney biopsy was performed in 14 patients. Lupus nephritis was found in 5 patients. Twelve patients received a bolus of methylprednisolone, 7 patients required intravenous cyclophosphamide, and only 1 patient was treated with rituximab. One-hundred twenty-nine patients underwent dialysis, and 554 patients benefited from telemedicine during this period. Conclusion Data collected in this study highlights that the global pandemic due to COVID-19 had a great impact on the activity of our department. The continuity of care for our patients has been ensured by the implementation of telemedicine and the reorganization of our hospital activity.